Patriotyzm jako wartość w serialu telewizyjnym na przykładzie „Czasu honoru. Powstanie” - Molicka, Paulina (Wydawnictwo Uniwersytetu Rzeszowskiego, 2018)
This article is devoted to the issue of valuation in a television series. The exemplification material comes from the popular Polish production “Czas honoru. Powstanie”. The text aims to present representative examples – mainly the attitudes of young people who can be a model for modern generations of Poles.
Keywords: television series; patriotism; values; attitudes